PENENTUAN FLUIDA HIDROKARBON DAN KONTAK FLUIDA BERDASARKAN ANALISIS KROMATOGRAFI GAS RESERVOAR GABUS 1, LAPANGAN NB, CEKUNGAN NATUNA BARAT - , Boy Wibowo Pangarso; , Dr. Ir. Jarot Setyowinoto, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of the subsurface data acquisition type during a well drilling activity is mudlogging. This data acquisition method is regularly conducted either in exploration or development drilling. Mudlogging is basically an activity to continuously monitor drill cuttings that is transported to the surface during drilling activity. This type of data could be utilized for hydrocarbon evaluation. Gas chromatography data is one of the output from mudlogging activities. This data could be use to interpret fluid contacts and fluid type in the formation. The objective of this research is to obtain gas chromatograph ratio to determine fluid type and hydrocarbon contact in the Gabus â 1 reservoir in NB field. This gas ratio method will be integrated and validated by petrophysical analysis result, formation pressure analysis and PVT analysis result conducted in the laboratory. This research is using a different approach compared to previous methods, which in this research, not only mudlogging data is being utilised but also petrophysical analysis results such as Vshale, Porosity and Water Saturation derived from log curve data such as GR, Resistivity, Neutron and Density, to validate results of gas ratio method. Other interpretation utilised to validate gas ratio result is crossplot of formation pressure to obtain fluid type and hydrocarbon contact. Secondary data utilised to validate the gas ratio result is PVT analysis on bottom hole sample conducted in the laboratory. Based on the result from gas chromatograph ratio integrated and validated with electric log, formation pressure and PVT interpretation, four different fluid compartments with different contacts were identified in NB field. Fluid types were identified as gas, oil and water. PVT analysis result is consistent with interpretation from gas chromatograph ratio analysis.